ANALISIS KINERJA PEGAWAI NEGERI SIPIL PADA DINAS SOSIAL KOTA PALANGKA RAYA - Robert Fransiska (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2018)
This research purposes to desribe motivation, discipline and leadership in the Departemet of the distric Social in Palangka Raya city. The sampling chooses 69 officer to be teken the number of population 218 officers, sampling technic to use Proportional random sampling. The research instrument chooses questioner, to be built in 1-5 scale, score 1 for very bad reaction, and score 5 for very good reaction. The technic of the date analysis chooses descriptive analysis and doble regrasi analysis.The result of this research show both motivation and discipline of the officers in the Department of the Distric social in Palangka Raya city Regency can be categoried good. The Main motivation of the officer to be supported by the high of the opportunity to built self potency to work, whereas discipline to be shown by the acceptance of the officer will be punished if the break the rule anthe arrangement to be used even the leadership the behavior has done dominance in the usual organization is delegatif behavior.The result of hipotesis show that motivation, discipline and leadership to be proved positive in influence and significant to carrier of the officer and among variable of motivation, discipline and leadership to appear motivation is a dominant variable to influence the carrier of the officer in  the Department Of The Distric social in Palangka Raya city.